2001
DOI: 10.1139/f01-136
|View full text |Cite
|
Sign up to set email alerts
|

Successful recovery of the physiological status of coho salmon on board a commercial gillnet vessel by means of a newly designed revival box

Abstract: Successful application of fish-revival techniques in commercial fishing prior to release of nontarget species requires clear evidence that recovery devices do indeed improve physiological status and minimize postcapture delayed mortality. This study provides such evidence for a newly designed recovery box (Fraser box) that assisted gill ventilation. Immediately after capture by gillnet, adult coho salmon (Oncorhynchus kisutch) were in a state of severe metabolic exhaustion and stress, based on a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
134
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(148 citation statements)
references
References 34 publications
10
134
4
Order By: Relevance
“…fontinalis (Milligan et al , ; Kieffer et al , ), and can accelerate recovery in wild O . kisutch after capture with commercial fishing gear (Farrell et al , ). The mechanisms that accelerate recovery are poorly understood, but may involve cortisol dynamics or oxygen delivery improvements (Milligan et al , ; Kieffer et al , ).…”
Section: Locomotionmentioning
confidence: 99%
“…fontinalis (Milligan et al , ; Kieffer et al , ), and can accelerate recovery in wild O . kisutch after capture with commercial fishing gear (Farrell et al , ). The mechanisms that accelerate recovery are poorly understood, but may involve cortisol dynamics or oxygen delivery improvements (Milligan et al , ; Kieffer et al , ).…”
Section: Locomotionmentioning
confidence: 99%
“…Farrell et al [28] found that non-target wild coho salmon (Oncorhynchus kisutch) captured by troll, seine and gill net showed signs of severe metabolic exhaustion at the time of capture, raising concerns over the likelihood of post-release survival. To address this concern, methods for facilitating and expediting physiological recovery were tested [28] and refined [29,30]. The idea of promoting recovery from fisheries capture stemmed from results of Milligan et al [31], who provided evidence for accelerated metabolic recovery from exhaustive exercise in the laboratory of hatchery-reared rainbow trout (Oncorhynchus mykiss) when they were recovered in flowing water while swimming at constant velocity (i.e.…”
Section: Fisheries Gear Interactions (A) Problem Statementmentioning
confidence: 99%
“…This application of the results of the Milligan et al [31] study was expanded to the commercial troll fishery where Farrell et al [30] found that placing fish in a cage/net pen towed alongside the moving vessel resulted in rapid physiological recovery and no mortality during the 24 h assessment period. Facilitated recovery using a revival box, called the Fraser Box after the commercial fisher who constructed the first prototypes, successfully promoted physiological recovery, rapidly restoring swimming ability in 1-2 h, and resulted in high post-release survival, even for fish that appeared moribund at the time of gill net capture [29]. The survival benefit of the Fraser Box has resulted in these recovery boxes being implemented in marine commercial fisheries for releasing coho salmon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al . (2003 a ) measured critical swimming velocities and exercise‐associated oxygen consumption rates in ocean‐ranched and transgenic coho salmon and Farrell et al . (2001 a , b ) measured the physiological consequences of troll‐capture and vessel‐based recovery in wild coho salmon.…”
Section: Introductionmentioning
confidence: 99%